2009
DOI: 10.1002/pssr.200903121
|View full text |Cite
|
Sign up to set email alerts
|

Two modes of electroluminescence from single‐walled carbon nanotubes

Abstract: The electroluminescence from single‐walled carbon nanotube field effect transistors is spectrally resolved, and shows two distinct modes of light emission. The vast majority of nanotubes have spectrally broad emission consistent with the spectrum of blackbody radiation. Much more rarely, superposed on the broad emission is a single narrow (<50 meV) peak which is consistent with expectation for electron–hole recombination. The narrow emission is strong even at lower biases and in general has greater peak int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…We can thus exclude impact excitation 36 as a source of electroluminescence, which was previously observed for unipolar and short-channel SWNT network FETs. 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can thus exclude impact excitation 36 as a source of electroluminescence, which was previously observed for unipolar and short-channel SWNT network FETs. 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…We can thus exclude impact excitation 36 as a source of electroluminescence, which was previously observed for unipolar and short-channel SWNT network FETs. 37,38 Importantly, in the ambipolar regime, when the emission zone is positioned within the channel and several micrometers away from the electrodes, the electron and hole currents are perfectly balanced because all injected charges must recombine either radiatively or nonradiatively, and thus a given drain current always results in a corresponding number of excitons. Recording near-infrared (800−1600 nm) electroluminescence images for a gate voltage sweep at a constant drain current (see Supporting Information Figure S4) and assigning to each pixel the maximum intensity value during this sweep produces an electroluminescence map as previously shown for light-emitting polymer FETs 39 and can be directly compared to photoluminescence images from the same area (see Figure 2f−h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Luckily, SWCNTs retain many of their advantageous properties in aligned or random networks and are thus also interesting for thin film optoelectronics . Even in the early days of nanotube research, transistors with networks or thin films of SWCNTs showed electroluminescence . However, the presence of residual metallic nanotubes and lack of control over the network composition (i.e., many nanotubes with different diameters and bandgaps) complicated the interpretation of these early nanotube thin film LEFETs.…”
Section: Lateral Single Layer and Ambipolar Lefetsmentioning
confidence: 99%
“…The earliest and most common approach is to build an image pixel by pixel by raster scanning a focused spot [1][2][3][4]. More recently, faster global imaging approaches have been used with fluorescence [5][6][7][8], Raman [9], and electroluminescence [10][11][12]. These approaches are like classical far-field optical microscopy, in which an entire image is obtained instantaneously.…”
Section: Introductionmentioning
confidence: 98%